Quantifying the drivers of HIV transmission and prevention in men who have sex with men: a population model‐based analysis in Switzerland. Issue 10 (26th July 2018) - Kusejko, K; Marzel, A; Hampel, B; Bachmann, N; Nguyen, H; Fehr, J; Braun, DL; Battegay, M; Bernasconi, E; Calmy, A; Cavassini, M; Hoffmann, M; et al.
Abstract : Objectives: Despite the huge success of antiretroviral therapy (ART), there is an ongoing HIV epidemic among men who have sex with men (MSM) in resource‐rich countries. Understanding the driving factors underlying this process is important for curbing the epidemic. Methods: We simulated the HIV epidemic in MSM in Switzerland by stratifying a mathematical model by CD4 count, the care cascade and condom use. The model was parametrised with clinical, epidemiological and behavioural data from the Swiss HIV Cohort Study and surveys in the HIV‐negative population. Results: According to our model, 3.4% of the cases that would otherwise have occurred in 2008–2015 were prevented by early initiation of ART. Only 0.6% of the cases were attributable to a change in condom use in the HIV‐positive population, as less usage is mainly seen in virally suppressed MSM. Most new infections were attributable to transmission from recently infected undiagnosed individuals. It was estimated that doubling the diagnosis rate would have resulted in 11.8% fewer cases in 2001–2015. Moreover, it was estimated that introducing pre‐exposure prophylaxis (PrEP) for 50% of those MSM not using condoms with occasional partners would have resulted in 22.6% fewer cases in 2012–2015. Conclusions: By combining observational data on the relevant epidemiological and clinical processes with a mathematical model, we showed that the 'test and treat' approach is most effective in reducing the number of new cases. Only a moderate population‐level effect was estimated for early initiation of ART and a weak effect for the change in condom use of diagnosed MSM. Protecting HIV‐negative individuals who are not using condoms with PrEP was shown to have a major impact.